Pemetaan Sektor Agribisnis Pangan Unggulan di Kabupaten Musi Rawas - Zaini Amin; Andry Andry; Edy Humaidi (Jurnal Penelitian Pertanian Terapan, 2021)
This study aims to map food commodities that are feasible to develop in Musi Rawas Regency. The method of calculation used to determine superior and non-superior commodities is the Location Quotient (LQ) method. The data used includes secondary data obtained from the Central Statistics Agency and the Department of Agriculture and Animal Husbandry of Musi Rawas Regency in 2019, as well as primary data from interviews with farmers. The results showed that of the eight food commodities, there were 6 which were superior commodities, namely lading rice, sweet potato, maize, peanuts, green beans, and soybeans, while the other two, namely lowland rice and cassava, were non-superior food commodities.